Work orientation: Dimensionality and internal model - Pitacho, Liliana Alexandra (2019)
In this study, we investigate the dimensionality of work orientation and propose an internal model. Our study considers the model of work orientation presented by Bellah et al. (1985). This model assumes that there are three types of work orientation: calling, career, and job. We undertook a transversal study of 959 Portuguese adults between the ages of 18 and 71, who were all currently working. We used confirmatory factor analysis to study the dimensionality of work orientation and, to study the internal model of work orientation, we used structural equation modelling. Together, the results of these analyses suggest that work orientation is indeed three-dimensional and, additionally, suggest that work orientation dimensions have a direct impact on each other. This study provides important contributions to the theory of work orientation and introduces for discussion and future research an even greater set of questions.